(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Indiabeing a democratic country has made the elementary education a fundamentalright of all citizens. The Supreme Court of India has also felt the needs ofelementary education and in a judgment held that all citizens have afundamental right to education up to the age of 14 years.